Glucosinolate and phenylpropanoid biosynthesis are linked by proteasome‐dependent degradation of PAL. Issue 1 (11th September 2019) - Kim, Jeong Im; Zhang, Xuebin; Pascuzzi, Pete E.; Liu, Chang‐Jun; Chapple, Clint
Summary: Plants produce several hundreds of thousands of secondary metabolites that are important for adaptation to various environmental conditions. Although different groups of secondary metabolites are synthesized through unique biosynthetic pathways, plants must orchestrate their production simultaneously. Phenylpropanoids and glucosinolates are two classes of secondary metabolites that are synthesized through apparently independent biosynthetic pathways. Genetic evidence has revealed that the accumulation of glucosinolate intermediates limits phenylpropanoid production in a Mediator Subunit 5 (MED5)‐dependent manner. To elucidate the molecular mechanism underlying this process, we analyzed the transcriptomes of a suite of Arabidopsis thaliana glucosinolate‐deficient mutants using RNAseq and identified misregulated genes that are rescued by the disruption of MED5. The expression of a group of Kelch Domain F‐Box genes ( KFB s) that function in PAL degradation is affected in glucosinolate biosynthesis mutants and the disruption of these KFBs restores phenylpropanoid deficiency in the mutants. Our study suggests that glucosinolate/phenylpropanoid metabolic crosstalk involves the transcriptional regulation of KFB genes that initiate the degradation of the enzyme phenylalanine ammonia‐lyase, which catalyzes the first step of the phenylpropanoid biosynthesis pathway. Nevertheless, KFB mutant plants remain partially sensitive to glucosinolate pathway mutations, suggesting that other mechanisms that link the two pathways also exist.